Highly Efficient Methods to Culture Mouse Cholangiocytes and Small Intestine Organoids - Chen, Wenyi; Yao, Qigu; Wang, Ruo; Fen, Bing; Chen, Junyao; Xu, Yanping; Yu, Jiong; Li, Lanjuan; Cao, Hongcui (Frontiers in Microbiology, 2022)
Background: Organoids, which enable disease modeling and drug screening closer to the in vivo environment, can be isolated and grown from organs such as brain, small intestine, kidney, lung, and liver. To facilitate the establishment of liver and small-intestinal organoids, we developed an efficient protocol for collecting cholangiocytes and intestine crypts and culturing organoids. Methods: Cholangiocytes were collected from intrahepatic bile ducts, gallbladder, and the small intestine crypts by gravity settling and multi-step centrifugation methods. The cell isolated were embedded with Matrigel and grew into three-dimensional spheroids in suitable culture medium. The stability of organoid cells was assessed by subculture, cryopreservation, and thawing. RNA and DNA extraction of organoids, as well as immunostaining procedure were also optimized. Hand-picking procedure were developed and performed to ensure the similar growth characteristics of organoids. Results: Large amount of Cholangiocytes and small intestine crypts were collected under this protocol. Cholangiocytes developed into cyst-like structures after 3–4 days in Matrigel. After 1–2 weeks cultivation, small-intestinal organoids (in-orgs) developed buds and formed a mature structure. Compared to organoids derived from gall bladder, cholangiocytes-organoids (cho-orgs) from intrahepatic bile ducts grew more slowly, but had a longer culture-term, expressed the cholangiocyte markers Krt19 and Krt7, and recapitulated the in vivo tissue organization. Conclusions: This protocol simplified the cell collection procedure and avoided the possibility of exposing tissue derived stem cells to mechanical damage or chemical injury by gravity settling and multistep centrifugation. In addition, our approach allows similar growth characteristics of organoids from different mammalian tissue sources. The protocol requires 2–4 weeks to establish a stable organoid growth system. Organoids could be stably passaged, cryopreserved, and recovered under the protocol guidance. Besides, the organoids of liver and small intestine retained original tissue characteristics, such as tissue-specific marker expression, which prepares them for further experiments such as preclinical in vitro trials and mechanism research.